The effect of vacuum pressure on the flammability limits of natural gas (NG) - Lyna Liyana, Johar (2010)
The purpose of this study is to determine the effect of vacuum pressure on the flammability limits Natural Gas in a closed vessel explosionsat various initial pressures within 0.98 and 0.96 bar and at ambient initial temperature. Times and pressure of the explosions were recorded. Experimental investigations are conducted by systematically measuring the pressure histories in a constant volume 20-L- apparatus. In this experimental study, we analyzed and do the comparison with 3 various pressure, which is 1 bar, 0.98 bar and 0.96 bar. Experimental result shown that at 10 volume percent of concentration natural gas ,pressure maximum for 0.98 bar natural gas – air mixture is 5.1 bar and for 0.96 bar natural gas- air mixture is 4.7 bar. While compare with 1 bar natural gas – air mixture, pressure maximum is 5.8 bar. Flammability limits for 0.98 and 0.96 bar is still 5 to 15 percent of concentration. As a conclusion, by reducing the pressure of Natural Gas- air mixture will not effected the flammability limits range but it will be decreased the pressure maximum ( Pmax) of explosion.